Asian Journal of Gerontology and Geriatrics 2023
DOI: 10.12809/ajgg-2023-588-oa
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric care model for older patients with COVID-19 at a community treatment facility in Hong Kong

Abstract: Background. During the fifth wave of the COVID-19 pandemic in Hong Kong, a geriatric team was established to provide interdisciplinary intervention and discharge planning for older patients in a community treatment facility (CTF) at the AsiaWorld-Expo. This study examined clinical outcomes among these older patients and identified key determinants of these outcomes.Methods. Medical records of patients aged ≥60 years who were admitted to the CTF for management of COVID-19 by a geriatric team between 24 March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Therefore, it has been claimed that close friendships and social interaction with others outside the family and previous network are important for older persons' social needs and meaningfulness (Ashida & Heaney, 2008). In that respect, it has been reported that day care centres can fulfil social needs and offer a sense of social connectedness and belonging that counteracts loneliness (Carlsson et al, 2020; Hickerson et al, 2008; Miller, 2016; Orellana et al, 2020c; Walker et al, 2004) and that staff‐facilitated activities can enhance meaningfulness and well‐being of the elderly people (Seddigh et al, 2020; enhancing well‐being and quality of life (Fields et al, 2014; García‐Martín et al, 2004; Kwok et al, 2013; Miller, 2016; Orellana et al, 2020c; Pitkala et al, 2009; Svidén et al, 2004; Tollén et al, 2007). Nevertheless, it is still a mystery as to what attendees find meaningful in attending organised activities and especially what the staff experiences as meaningful and purposeful about the activities offered.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been claimed that close friendships and social interaction with others outside the family and previous network are important for older persons' social needs and meaningfulness (Ashida & Heaney, 2008). In that respect, it has been reported that day care centres can fulfil social needs and offer a sense of social connectedness and belonging that counteracts loneliness (Carlsson et al, 2020; Hickerson et al, 2008; Miller, 2016; Orellana et al, 2020c; Walker et al, 2004) and that staff‐facilitated activities can enhance meaningfulness and well‐being of the elderly people (Seddigh et al, 2020; enhancing well‐being and quality of life (Fields et al, 2014; García‐Martín et al, 2004; Kwok et al, 2013; Miller, 2016; Orellana et al, 2020c; Pitkala et al, 2009; Svidén et al, 2004; Tollén et al, 2007). Nevertheless, it is still a mystery as to what attendees find meaningful in attending organised activities and especially what the staff experiences as meaningful and purposeful about the activities offered.…”
Section: Introductionmentioning
confidence: 99%